Prinsip Pengembangan Sosial Emosional AUD di TK IT Hirshan Muda: Diterapkannya Sekolah Sehat Dalam Pendidikan Karakter - Farhanatul Kamilah, Rifa; Sianturi, Risbon; Suherman, Tiara; Sumiyati, Sumiyati (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2024)
This study aims to describe the principles of socio-emotional development of Early Childhood Education (ECE) at TK IT Hirshan Muda, Tasikmalaya, West Java, particularly in the context of the implementation of the Healthy School program. This descriptive qualitative research employed in-depth interviews with teachers and participant observation to collect data. The findings indicate that TK IT Hirshan Muda (Kota Tasikmalaya Jawa Barat) implements the principles of socio-emotional development of ECE through various programs, including positive behavior training (through training in the use of polite language, orderly lining up), constructive conflict resolution, empathy and cooperation development, emotion expression, stress management, independence development, and collaboration with parents through parenting programs and effective communication. The integrated Healthy School program significantly contributes to creating a positive learning environment and supporting the holistic development of early childhood, including the socio-emotional aspect. This study recommends replicating the socio-emotional development model integrated with the Healthy School program in other kindergartens